Genome-Wide Association Studies of Salt Tolerance at Seed Germination and Seedling Stages in Brassica napus - Zhang, Guofang; Zhou, Jinzhi; Peng, Yan; Tan, Zengdong; Li, Long; Yu, Liangqian; Jin, Cheng; Fang, Shuai; Lu, Shaoping; Guo, Liang; Yao, Xuan (Frontiers in Plant Science, 2022)
Most crops are sensitive to salt stress, but their degree of susceptibility varies between species and cultivars. In order to understand the salt stress adaptability of Brassica napus, we collected the phenotypic data of 505 B. napus accessions at germination stage under 150 mM or 215 mM NaCl and at seedling stage under 215 mM NaCl. We mapped 31 salt stress-related QTLs by genome-wide association studies (GWAS) of 16 salt tolerance coefficients (STCs) to investigate the genetic basis of salt stress tolerance of B. napus. A total of 177 and 228 candidate genes related to salt stress tolerance were detected at germination and seedling stage, respectively. Finally, overexpression of two candidate genes, BnCKX5 and BnERF3 overexpression, were found to increase the sensitivity to salt and mannitol stresses at germination stage. Theses candidate genes are rich genetic resources for the following exploration of molecular mechanism in adaptation to salt stress in B. napus. This study demonstrates that it is a feasible method to dissect the genetic basis of salt stress tolerance at germination and seedling stages in B. napus by GWAS, which provides valuable loci for improving the salt stress tolerance of B. napus.